Institutionalizing partnerships: a mixed methods approach to identifying trends and perceptions of community policing and multi-agency task forces. (15th January 2021) - Sedgwick, Donna; Callahan, Jason; Hawdon, James
ABSTRACT: Cooperation with citizens and community agencies is fundamental to successful community policing. Considerable scholarship has documented cooperation between police and residents; however, cooperation among police agencies at the local, state, and federal level is also important. We use a variety of methods to investigate if such multi-agency partnerships in the United States have become more common and, if so, why such cooperation occurs. In interviews, officers frequently report that the use of interagency collaboration increased as community policing became institutionalized. We then test our assertions using trend data to demonstrate that community policing and multi-agency joint task forces became increasingly popular since the terrorist attacks of 11 September 2001, and these trends are correlated at the departmental level. We contend that institutional pressures contribute both to the continued dominance of community policing as a policing style as well as the increasing occurrence of multi-agency task forces. This research has implications for policing in nations where numerous agencies comprise a fragmented system and policing decisions are made at the local level (e.g., Belgium, England, the Netherlands, U.S.) or other polycentric political communities such as the European Union.